Impact and recovery of the COVID‐19 pandemic on weight status of children and adolescents. Issue 2 (22nd January 2023) - Bond, Diana M.; Seimon, Radhika; Schneuer, Francisco J.; Baur, Louise A.; Craig, Maria; Alexander, Shirley; Garnett, Sarah P.; Henderson, Joanne; Nassar, Natasha
Summary: Recent evidence suggests the immediate effects of the COVID‐19 lockdowns and restrictions have resulted in increased weight in children and adolescents. However, the longer‐term effects have not been assessed. The aim of this study was to examine the impact and longer‐term effects of the COVID‐19 pandemic on BMI and weight status of children and adolescents. This study used routinely collected clinical data from the Sydney Children's Hospitals Network, comprising two socio‐demographically diverse children's hospitals in New South Wales, Australia from 2018 to 2021. Of 245 836 individuals ≤18‐years assessed, mean BMI percentile increased from 58.7 (SD 31.6) pre‐COVID‐19 to 59.8 (SD 31.7) ( p  < .05) post‐restrictions and overweight/obesity increased by 5.5% (obesity alone 6.3%), predominantly in children <12‐years and from lower socioeconomic backgrounds. The trend in BMI percentile was steady pre‐COVID‐19 ( β  = −0.03 [95% CI −0.07, 0.01]), peaked immediately following COVID‐19 restrictions ( β  = 1.28 [95% CI 0.24, 2.32]) and returned to pre‐pandemic levels over ensuing 21 months ( β  = −0.04 [95% CI –0.13, 0.04]). Routine anthropometric measurement facilitates ongoing monitoring and evaluation of the weight status of children and adolescents, helping to identify those at‐risk. Despite initial BMI and weight increases among children and adolescents, longer‐term follow‐up highlighted a return to pre‐pandemic rates, possibly attributed to state‐wide policies aimed at reducing childhood obesity.